Evaluation of environmental engineering and hydrology architecture of employee's flood resistance at PT XYZ, in a Peatland area - Pratama, Aldi Adi; Chirzun, Ahmad (Department of Civil Engineering Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Occupancy comfort is an essential factor for the owner. A critical aspect of occupancy is good housing resilience from various elements, from risk management in dealing with natural disasters and maintenance functions, such as the potential for flooding in areas prone to overflow. PT XYZ is a palm oil industry in western Indonesia with employee housing with a high potential for flooding because it is close to a waste treatment site and a river flow. Therefore, the owner of the company has plans to rebuild new housing. The process of building flood-resistant houses must be carried out so as not to cause more significant losses. This paper aims to provide an evaluation to the community, especially company stakeholders, to prioritize the analysis of potential flood risks before building multi-story residential structures in new housing. Observations using the hand drill approach showed that the soil element of 3.63 g/cm3 peat experienced an increase in water content from 120% (1991) to 230% (2023). Stabilizing the red bricks that had been smoothed at the start of the construction were declared lost, making it prone to flooding and difficult to construct new residential buildings. The hydrological technique with eight experiments shows that the higher the number of gaps that occur, the higher the inundation around settlements, with a function of y = 0.2x – 0.01 and R² = 0.9767. Kenyamanan hunian merupakan faktor yang sangat penting bagi pemiliknya. Salah satu aspek yang perlu ada adalah memiliki ketahanan yang baik dari berbagai sisi, baik dari aspek manajemen risiko dalam menghadapi bencana alam maupun fungsi pemeliharaan, seperti potensi banjir di suatu kawasan rawan luapan. PT XYZ merupakan industri kelapa sawit di wilayah Indonesia bagian barat memiliki perumahan karyawan yang memiliki potensi banjir yang tinggi, karena letaknya yang dekat dengan tempat pengolahan limbah, dan aliran sungai. Oleh karena itu, pemilik perusahaan memiliki rencana untuk membangun kembali perumahan baru. Proses pembangunan perumahan yang tahan banjir harus dilakukan agar tidak menimbulkan kerugian yang lebih besar. Tujuan dari penulisan ini adalah untuk memberikan evaluasi kepada masyarakat khususnya stakeholder perusahaan agar mengutamakan analisis potensi resiko banjir sebelum membangun struktur hunian bertingkat di perumahan yang baru. Hasil pengamatan dengan pendekatan bor tangan menunjukkan bahwa unsur tanah gambut sebesar 3,63 gr/cm3 mengalami peningkatan kadar air dari 120% (1991) menjadi 230% (2023). Stabilisasi batu bata merah yang dihaluskan pada awal konstruksi dinyatakan hilang, sehingga rentan terhadap banjir dan sulit untuk membangun konstruksi tempat tinggal baru. Teknik hidrologi dengan 8 kali percobaan, menunjukkan bahwa semakin tinggi jumlah celah yang terjadi maka semakin tinggi genangan di sekitar hunian, dengan fungsi y = 0,2x – 0.01 dan R² = 0,9767.